Study of the Integrated Academic Building for Academic Development in the UIN Sunan Kalijaga - Muhammad Zamhari; Syaeful Arief; Awan Pramudya Wardhani; Zaim Shidiq; Siti Shofiyah (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2025)
The success of a construction project can be evaluated by its benefits. In 2022, UINSunan Kalijaga received support from the Sovereign Sharia Securities (Surat BerhargaSyariah Negara/SBSN) 2022 for the construction of the Integrated Academic Building(Gedung Kuliah Terpadu/GKT). This research aims to assess the extent of the benefitsof the GKT for academic services at UIN Sunan Kalijaga. A qualitative research methodwas employed for this study due to its naturalistic approach. The research findingsreveal that 75.58% of respondents strongly agree, and 54.21% agree that the GKTsupports academic development at UIN Sunan Kalijaga. These results indicate that theconstruction of the GKT, with its comprehensive facilities, provides significant benefitsto the academic community.